ASSESSMENT OF THE RADIATION-ECOLOGICAL STATE OF GROUNDWATER ON THE TERRITORY OF THE FORMER AZGIR TEST SITE IN WESTERN KAZAKHSTAN (Journal of Geography and Environmental Management, 2023)
The Azgir test site is one of the radiation hazardous facilities in Kazakhstan. At the test site, for research purposes, 17 underground nuclear explosions  were carried out in the period 1966-1979 to develop the technology of creating cavities for various purposes underground in the rock salt massif. As a result of the work carried out, 9 underground cavities of different volumes and at different depths were created.The article presents the results of studying the trace element and radionuclide composition of the ground water of the Azgir test site, taking into account new data obtained after drilling new observation wells in 2021. It is shown that the values of specific activities of artificial radionuclides in the water of the bore holes and wells under study are at the background level and are comparable with long-term data of radioecological monitoring at the test site, which indicates the absence of migration processes of radionuclides from underground nuclear cavities at the present time. The local collection of underground water of the test site is the "Uzhuntator" mulda, located between the salt domes of the Western and Eastern Azgir. The underground water of the test site also lie in separate disparate lenses.An assessment of the toxicity of waters from observation the bore holes and wells by the content of heavy metals in water using the heavy metal pollution index (HPI) is presented. The dominance of chemical elements in groundwater is established in the order Fe>Mn>Ni>Cr>Co>Mo>Cu>Zn. The conclusions about the unsuitability of these water for drinking purposes have been confirmed. The value of the HPI index is up to 72.6 times higher than the critical value for drinking water, which is due to the hydrogeological conditions of groundwater occurrence.The study was conducted on the basis of the Center of Complex Environmental Research of the RSE Institute of Nuclear Physics.
Keywords: groundwater; underground nuclear cavities; radionuclides; heavy metals; heavy metal pollution index; Azgir test site